Lipocalin‐type prostaglandin D synthase‐derived PGD2 attenuates malignant properties of tumor endothelial cells. Issue 1 (10th November 2017) - Omori, Keisuke; Morikawa, Teppei; Kunita, Akiko; Nakamura, Tatsuro; Aritake, Kosuke; Urade, Yoshihiro; Fukayama, Masashi; Murata, Takahisa
Abstract: Endothelial cells (ECs) are a key component of the tumor microenvironment. They have abnormal characteristics compared to the ECs in normal tissues. Here, we found a marked increase in lipocalin‐type prostaglandin D synthase (L‐PGDS) mRNA ( Ptgds ) expression in ECs isolated from mouse melanoma. Immunostaining of mouse melanoma revealed expression of L‐PGDS protein in the ECs. In situ hybridization also showed L‐PGDS (PTGDS) mRNA expression in the ECs of human melanoma and oral squamous cell carcinoma. In vitro experiments showed that stimulation with tumor cell‐derived IL‐1 and TNF‐α increased L‐PGDS mRNA expression and its product prostaglandin D2 (PGD2 ) in human normal ECs. We also investigated the contribution of L‐PGDS–PGD2 to tumor growth and vascularization. Systemic or EC‐specific deficiency of L‐PGDS accelerated the growth of melanoma in mice, whereas treatment with an agonist of the PGD2 receptor, DP1 (BW245C, 0.1 mg/kg, injected intraperitoneally twice daily), attenuated it. Morphological and in vivo studies showed that endothelial L‐PGDS deficiency resulted in functional changes of tumor ECs such as accelerated vascular hyperpermeability, angiogenesis, and endothelial‐to‐mesenchymal transition (EndMT) in tumors, which in turn reduced tumor cell apoptosis. These observations suggest that tumor cell‐derived inflammatory cytokines increase L‐PGDS expression and subsequent PGD2 production in the tumor ECs. This PGD2 acts as a negative regulator of the tumorigenic changes in tumor ECs. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.